2012
DOI: 10.1111/j.1600-0765.2012.01504.x
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate induces reactive oxygen species production and affects cell cycle progression in human gingival fibroblasts

Abstract: These results suggest that butyrate generated by periodontal pathogens may be involved in the pathogenesis of periodontal diseases via the induction of ROS production and the impairment of cell growth, cell cycle progression and expression of cell cycle-related genes in GFs. These events are important in the initiation and prolongation of inflammatory processes in periodontal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 36 publications
1
71
0
Order By: Relevance
“…S4a). Butyrate in the oral cavity is suggested to play a role in the development of periodontal disease [56,57]. Members of the genus Megasphaera are known to produce butyrate [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…S4a). Butyrate in the oral cavity is suggested to play a role in the development of periodontal disease [56,57]. Members of the genus Megasphaera are known to produce butyrate [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Short-chain fatty acids can disrupt host defense systems by different mechanisms, such as induction of apoptosis in immune cells (Stehle et al, 2001;Abe, 2012) and gingival epithelial cells (Tsuda et al, 2010) and alteration of cell function and gene expression in human gingival fibroblasts (Chang et al, 2013). Previous studies have demonstrated higher concentrations of short-chain fatty acids in the gingival crevicular fluid of periodontitis patients (Lu et al, 2008;Qiqiang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal pathogens produce butyrate and recently, butyrate was shown to participate in periodontitis development by inhibiting gingival fibroblast cell growth. Butyrate toxicity against human fibroblasts was attributed to increased reactive oxygen species produced by pathogenic bacteria (34). Other than butyrate, acetic acid and succinic acid were also found to be related to gingival inflammation (35).…”
Section: Discussionmentioning
confidence: 99%